Jaroslav Pelikan and the History of Theology - Avramov, Theodor (Forum Theologicum Sardicense, 2025)
The history of theology, especially in its contemporary aspect, is a surprisinglymethodologically undefined discipline. This article aims to draw insightsfrom Jaroslav Pelikan’s work and apply these findings as a tool tostudy Pelikan’s own thought, even if only very cursorily. The history oftheology is also examined as a discipline, and some avenues for its developmentare proposed.